DAMPAK KONFORMITAS TEMAN SEBAYA PADA MOTIVASI BELAJAR ANAK ASUH DI PANTI ASUHAN AISYIYAH MANINJAU - Vani Rahma Fitrah; Budi Santosa; Syawaluddin; Sri Hartati (STKIP Subang, 2026)
This research is motivated by the existence of peer conformity factors that have an impact on the learning motivation of foster children. Learning motivation is closely related to peer conformity, because adolescents are individuals who depend on groups. This study uses descriptive qualitative research that aims to describe the impact of peer conformity on the learning motivation of foster children at the Aisyiyah Maninjau Orphanage. Data collection in this study used interviews and observations. Interviews were conducted by asking questions directly to informants consisting of key informants, namely 1 caregiver and supporting informants, namely 6 foster children. The results of this study reveal that peer conformity can influence the learning motivation of foster children, with varying impacts depending on group dynamics and norms, so that it can produce positive or negative effects on learning motivation.